Biological activity of the implant for internal fixation; Journal of Tissue Engineering and Regenerative Medicine; Vol. 12, iss. 12 - Popkov A. V. Arnold Vasiljevich; Popkov D. A. Dmitry Arnoldovich; Kononovich N. A. Nataljya Andreevna; Gorbach E. N. Elena Nikolaevna; Tverdokhlebov S. I. Sergei Ivanovich; Bolbasov E. N. Evgeny Nikolaevich; Darvin E. O. Evgeny Olegovich (2018, 2018)
Title screen